Potential threats and socio-economic contradictions in the context of the smart city formation - M. N. Rybina; E. N. Bykovskaya (Вестник университета)
A study of Smart City functioning leads to the conclusion that Fourth Industrial Revolution poses threatening challenges, which require the close attention of scientists to eliminate existential threats to humanity and turn the Smart City functioning into a human centred system. The analysis of indicators and descriptors that determine the content of the smart city phenomenon and the essence of this concept remains relevant nowadays. The purpose of the article is to analyse the Smart Cities global network, countries, regional clusters and the urbanisation scale for the possible potential threats emergence to the artificial intelligence application in the Smart City: socio-economic, ethical, psychological, environmental and political. Using the methods of foresight, benchmarking and comparative analysis the authors have formulated and revealed the content of the political and reputational nature threats. These threats are linked to increasing polarisation in society, “hybrid” wars emergence, personal data losses, the labour market and employments problems, increasing ecological pressure on the environment and the line blurring between machine and human. The results of the study contribute to knowledge about the potential and negative aspects of the information technologies use in urban environments.